The importance of the order of addition of ingredients in the natural rubber (NR) mixing process: A qualitative analysis through molecular modeling - da Costa , Helson Moreira; Ramos , Valéria Dutra (Seven Editora, 2023)
The order of addition of ingredients in an elastomeric formulation of natural rubber was investigated using molecular modeling and the hypothetical adsorption process. Two sequences were evaluated, the zinc oxide system (ZnO) and the stearic acid system (C18), through the AMBER force field methodology. The theoretical data allow us to suppose that, although there is no statistically relevant difference between the adsorption energies, the C18 system does not seem to bring advantages in its adoption while the ZnO system only seems to be effective when the sequence suggested by the ASTM standard is obeyed. A seemingly ideal addition order in the ZnO system is suggested, but the nature of the adsorption process is changed, as is the arrangement of the additives. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-073